Analisis Minat Siswa Dalam Mengikuti Kegiatan Ekstrakurikuler Olahraga di SMK Negeri Nusawungu - Ahmad Zakaria; Teguh Priadi (Lembaga Pengembangan Kinerja Dosen, 2021)
This research is descriptive research which aims to determine students' interest in participating in extracurricular activities at Nusawungu State Vocational School students. The design used in this research is associative research with descriptive analysis methods. The population is all Class 2 students of Nusawungu State Vocational School, the total population is 279 people. Samples were taken using the Stratified Proportional Random Sampling technique, namely a tiered random sampling method taken from 10% of the total population. So the sample used could be as many as 30 students. The data analysis technique used is descriptive analysis of descriptive data, percentage analysis using a computer application through the SPSS 16 program. Based on the results of validity and reliability tests, all data is declared reliable because the correlation value (Cronbach's Alpha) on average 0.830 is considered good for use. Normality test The data was also declared normal with an Asymp value = 0.974 (p>0.05). Thus, the results obtained can be concluded that students' interest in taking extracurricular sports lessons at the Nusawungu State Vocational School shows the high category with the results obtained being 78.53%.